Pengaruh Kepuasan Pelanggan, Kepercayaan Pelanggan, Dan Switching Barriers Terhadap Loyalitas Pelanggan (Studi Kasus Steak Moen-Moen Malang) - Kristianti Arum Murdayah; Nur Hidayati; M. Khoirul Anwarudin Broto Suharto (UNIVERSITAS ISLAM MALANG, 2023)
Abstract This study aims to analyze the effect of Customer Satisfaction, Customer Trust and Switching Barriers on Customer Loyalty. The sampling method used is accidental sampling. The population of this study was the overall customers of Steak Moen-Moen Malang and the sample number was 75 respondents. The analysis used is multiple linear regression. The results showed that Customer Satisfaction and Customer Trust did not significantly affect Customer Loyalty, while the variable Switching Barriers had a significant effect on Customer Loyalty. Keywords: Customer Satisfaction, Customer Trust and Switching Barriers, Customer Loyalty